Circulating VE-cadherin in patients with controlled chronic lymphocytic leukemia - 10.14739/2310-1237.2014.2.28551 (Patologìâ)
Aim. To evaluate the prognostic value of circulating VE-cadherin for cumulative survival in asymptomatic coronary artery disease patients with full or partial remission of limphoproliferative diseases.